PERKEMBANGAN TERKINI DALAM DIAGNOSIS DAN PENATALAKSANAAN IRRITABEL BOWEL SYNDROME - Mariadi, I Ketut; Wibawa, I Dewa Nyoman (journal of internal medicine, 2007)
Irritable bowel syndrome (IBS) is a common gastrointestinal (GI) motility and sensory disorder that ischaracterized by abdominal pain/discomfort, bloating and altered bowel habit. The disease accounts for hugecosts for both patients and health-care systems and worsens significantly patients’ quality of life. Diagnosis isbased on the identification of symptoms according to Manning, Rome I and Rome II criteria and the most recentRome III criteria and exclusion of alarm indicators. The treatment of IBS is centred on an excellent doctor–patient relationship along with drugs targeting the predominant symptom, especially during exacerbations. Thisreview aim to explain new ctriteria to diagnose IBS and to conduct a systematic evidence-based review ofpharmacological therapies currently used, or in clinical development, for the treatment of IBS